Characterization of BiP Genes from Pepper (Capsicum annuum L.) and the Role of CaBiP1 in Response to Endoplasmic Reticulum and Multiple Abiotic Stresses - Wang, Hu; Niu, Huanhuan; Zhai, Yufei; Lu, Minghui (Frontiers in Plant Science, 2017)
Adverse environmental conditions have a detrimental impact on crop growth and development, and cause protein denaturation or misfolding. The binding protion (BiP) plays an important protective role by alleviating endoplasmic reticulum (ER) stress induced by misfolded proteins. In this study, we characterized three BiP genes (CaBiP1, CaBiP2 and CaBiP3) in pepper, an economically important vegetable and spice species. The role of CaBiP1 in plant tolerance to ER stress and adverse environmental conditions (including heat, salinity, osmotic and drought stress) were investigated. All the expected functional and signaling domains were detected in three BiP proteins, but the motifs and exon-intron distribution differed slightly in CaBiP3. CaBiP1 and CaBiP2 were constitutively expressed in all the tested tissues under both normal and stressed conditions, whereas CaBiP3 was mainly expressed following stress. Silencing of CaBiP1 reduced pepper tolerance to ER stress and various environment stresses, and was accompanied by increased H2O2 accumulation, MDA content, relative electric leakage, water loss rate, and a reduction in soluble protein content and relative water content in the leaves. Conversely, overexpression of CaBiP1 in Arabidopsis enhanced tolerance to ER stress and multiple environment stresses, as demonstrated by an increase in germination rate, root length, survival rate, soluble protein content, relative water content, the unfolded protein response (UPR) pathway, and a decrease in water loss rate. Our results suggest that CaBiP1 may contribute to plant tolerance to abiotic stresses by reducing ROS accumulation, increasing the water-retention ability, and stimulating UPR pathways and expression of stress-related genes.